LGALS3BP: A Potential Prognostic Biomarker Influencing Antitumor Immunity in Triple-negative Breast Cancer - Hu, Anqi; Pan, Shuaikang; He, Yuan; Wang, Xueru; Qian, Dong; Li, Xiaoyang (Current Medicinal Chemistry, 2025)
ObjectiveLGALS3BP exhibits differential expression in various types of tumors. This study aimed to analyze its potential diagnostic and prognostic value in Triple-negative Breast Cancer (TNBC).MethodsWe conducted a comprehensive analysis of LGALS3BP's differential expression and its association with patient survival outcomes using data from public databases. To further validate these findings, Immunohistochemistry (IHC) experiments were performed to confirm the differential expression of LGALS3BP protein in TNBC. Additionally, we also investigated the relationship among LGALS3BP, tumor immune infiltration, and drug sensitivity.ResultsResults indicated LGALS3BP to be significantly upregulated in TNBC, with its high expression correlating with improved survival outcomes. Furthermore, LGALS3BP expression correlated with immune cell infiltration. Notably, high LGALS3BP expression may confer a greater likelihood of benefiting from immunotherapy.ConclusionLGALS3BP may serve as a diagnostic and prognostic biomarker for TNBC.
Keywords: prognostic marker